The Role of Moral Leadership among Public School Principals in Developing Teachers’ Creative Skills - Obied , Asem (Dirasat: Educational Sciences, 2021)
The study aims to identify the role of moral leadership among public school principals in developing creative skills of teachers in Ramallah and Al-Bireh governorate from the teachers’ point of view, according to the variables: gender, educational qualification, and years of service. The researcher designed a questionnaire consisting of 44 items distributed over four domains. These are characteristics of personal ethical leadership, ethical leadership behaviors, ethical leadership characteristics related to human relations, and development of creative skills. The sample also consisted of 351 male and female teachers, who were chosen randomly. The study used a descriptive survey method. The results showed that school teachers’ responses to the role of moral leadership among public school principals in developing the creative skills of teachers in Ramallah and Al-Bireh governorate were moderate on all of the domains of the study. The results also revealed that there were differences in creative skills development due to educational qualification in favor of bachelor’s and master’s qualifications. The study recommends the necessity of encouraging educational leaders to practice good ethics to enhance creativity among teachers.